La práctica de los fundamentos básicos del basketbol influyen en el mejoramiento del equipo de selección de la unidad educativa Santa Juana de Arco La Salle de la ciudad de Cariamanga - Andrade Alverca, Holguer Edmundo (2014)
his research addresses the practice of the basic fundamentals of basketball influence in improving the selection team St. Joan of Arc Education Unit La Salle Cariamanga city of the province of Loja. The overall objective is to establish the incidence of the basics in preparing for the discipline of a competitive basketball team process improvement and selection of St. Joan of Arc Education Unit La Salle and specific objectives as study the most appropriate basis for good competitive team and improved selection of students in the seventh year of primary education and establish the level of knowledge possessed by each of the teachers of physical training on the ignorance of the basic fundamentals of basketball process. The research hypotheses were Ignorance of the basic fundamentals of basketball influences well to get positive results and improvement in its selection of St. Joan of Arc Education Unit The Salle. The methodological processes used by physical education teachers to practice the basics impact on improving team selection St. Joan of Arc Education Unit The Salle Cariamanga City and The impact of the application of the practice of the fundamentals of basketball in the improvement of the selection team of the institution benefited. The instruments used were survey in which a model survey of Teachers of Physical Culture and team selection St. Joan of Arc Education Unit The Salle was applied. In this project we will also find the fundamentals of basketball, passing, shooting or throwing basket, as well as technical fundamentals of basketball. You will also find the results to the respective tables with statistical analysis and interpretation graphics finally find the conclusions and recommendations for all who want to learn about this sport.